THE EVOLUTION OF DISCONTENT: ANGRY YOUNG MEN LITERATURE IN THE 21ST CENTURY - Chinakov Abdulahad Mo‘minjon ugli (TADQIQOTLAR, 2025)
Abstract  The  "Angry  Young  Men"  literary  movement  emerged  in  mid-20th century Britain, representing a generation's discontent with post-war socio-political realities. This study investigates how the themes of alienation, rebellion, and frustration have evolved in 21st-century literature. Focusing on contemporary authors such as Mohsin  Hamid,  Aravind  Adiga,  Dave  Eggers,  and  Ocean  Vuong,  the  research compares modern works with the classics of Osborne and Amis. The study reveals that while  the  socio-political  context  has  shifted,  core  themes  of  class  conflict, technological alienation, and identity struggles persist. Furthermore, modern literary techniques,  such  as  multivocal  narratives  and  nonlinear  storytelling,  enhance  the relevance and inclusivity of the Angry Young Men tradition in a globalized, digital world.